« Pour que maman ne parte pas si loin » - Gaspard Bouhallier (Histoire, Médecine et Santé, 2022)
This article reconsiders a social mobilization that took place in the psychiatric hospitals of the Seine Department at the beginning of 1948. In order to fight against a prefectoral project whose aim was to eliminate the psychiatric hospitals of Moisselles and Perray-Vaucluse, the families of the patients and the nurses of the psychiatric hospitals got involved in “defense committees” organized by the unions. Though heterogeneous, these committees denounced not only the proposed abolition of the Institutions, which, according to them, would have led to the transfer of patients to hospitals located in the provinces, but also the policy of public spending cuts that justified the project. The event thus highlights an opposition between two logics: that of the Department civil servants and elected officials bound by their budget requirements, and that of families and nurses claiming that the transfers would be harmful to the patients’ health.